Removal of Oil and Grease from Oily Kitchen Wastewater by Using Raw Kapok as a Potential Adsorbent - Abdul Hamid, Nor Hazren; Termizi, Nur Hanis Arina (Journal of Advanced Industrial Technology and Application, 2024)
Oil and grease are one of the elements that are poisonous and easily pollute the environment, especially water and soil. Adsorption techniques use natural adsorbents that do not damage or pollute the environment. The raw kapok was chosen as an adsorbent because it is a technology to overcome the problem of oil produced globally. The experiment was conducted with two types of dosage which are 5g and 15g of raw kapok to absorb the oil and the results stated that raw kapok can absorb the cooking oil that is still not used more than the cooking oil that has been used. Due to the density of the oils, it affects the ability of raw kapok to absorb and hold oil. In addition, this absorbed oil restores several water parameters such as dissolved oxygen (DO), pH, temperature and turbidity.